Dilemma of Legal Protection for TNI Soldiers Due to the Legal Vacuum in Military Administrative Procedure Regarding Litigation Mechanisms and Non-Litigation Options - Angling, Angling; Isretno Israhadi, Evita (Green Publisher Indonesia, 2024)
This research addresses the legal vacuum experienced by TNI soldiers due to the absence of a Government Regulation governing military administrative procedural law, as mandated by Law Number 31 of 1997 on Military Justice. The study aims to analyze the impact of this legal uncertainty on soldiers' access to justice, particularly those who feel aggrieved by military administrative decisions, while highlighting real-life examples of the challenges they encounter in pursuing justice. A normative juridical method with a descriptive-analytical approach is employed to examine relevant legal materials, cases, and theoretical frameworks. The results reveal significant legal uncertainty that creates barriers for soldiers to challenge administrative decisions effectively, leading to a lack of clarity in resolving disputes and protecting their rights. The findings underscore the urgent need for policy interventions, including issuing clear and comprehensive regulations on military administrative procedural law and establishing a specialized institution dedicated to handling such disputes. In conclusion, this research emphasizes the importance of addressing the legal vacuum to strengthen the legal system, ensure fairness, and safeguard the rights of TNI soldiers in Indonesia.